A COMPARATIVE STUDY OF THE PHYTOCHEMICAL, FREE RADICAL SCAVENGING AND ACID NEUTRALIZING POTENTIAL OF ETHANOL, ETHYL ACETATE, CHLOROFORM AND HYDROALCOHOLIC EXTRACT OF IPOMOEA RENIFORMIS CHOISY - SAO, ANIL PARASNATH; LOKSH, KAVITA; JAIN, GAURAV; YADUWANSHI, PHOOLSINGH (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Objective: This study aimed to provide comparative evidenced of chloroform (CE), ethyl acetate (EA), ethanol (EE) and hydroalcoholic (HE) extract of leaves of Ipomoea reniformis Choisy belonging to Convolvulaceae for its free radical scavenging, acid neutralizing potential and phytochemical property. Methods: The shade-dried leaves was extracted using Soxhlet apparatus and the extracts were subjected to determine phytochemical constituents, Antioxidant capacity by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) scavenging method and acid neutralizing capacity for artificial gastric juice. A high resolution trinocular microscope equipped with camera was used to assess microscopical characteristics of transverse section of leaves. Results: All four extract showed presence of glycosides, flavonoids, tannins, proteins and carbohydrates in abundance. Total phenolic content was highest 28.12±1.08 for EE extract measured in milligrams of gallic acid equivalent. Total flavonoids content was highest in EE 59.09±1.87 measured in milligrams of Rutin Equivalent per g of extract equivalent. The free radical scavenging potential can be acknowledged due to strong IC50 value of 52.24 µg/ml for EE extract using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) dye and had the highest antioxidant activity, measuring 94.84±1.56% at 1000 µg/ml. The pH of extracts was 1.69, highest for EE extract. Similarly the consumed volumes of extract to neutralize artificial gastric juice to pH 3.0 was significantly better for EA and EE extract ranging 9.36±0.09 ml and 10.56±0.09 ml respectively, indicating high antacid potency. Conclusion: Ipomoea reniformis Choisy leaf extract showed remarkable antioxidant capacity may be due to presence of phenols and flavonoids in higher concentrations and tends to possess positive gastric cytoprotection and ulcer healing potential.